Preparation method of high-entropy alloy powder and preparation method of obtained powder and coating

Through specific preparation methods and spraying processes, the problem of insufficient performance of FeCoNiMnAl high-entropy alloy in plasma spraying process is solved, and a high-entropy alloy coating with high mechanical properties, corrosion resistance and wave absorption characteristics is achieved, which is suitable for high-frequency and high-temperature environments.

CN120205827AActive Publication Date: 2025-06-27CHINA MACHINE KAIBO SURFACE TECHNOLOGY (JIANGSU) CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510686510.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-27
Publication Date
2025-06-27
Estimated Expiration
2045-05-27

AI Technical Summary

Technical Problem

FeCoNiMnAl high-entropy alloy has problems with poor mechanical properties, corrosion resistance and poor binding properties with substrate during plasma spraying.

Method used

A specific preparation method is used to prepare FeCoNiMnAl high-entropy alloy powder, including mixing metal precursor powder, binder and dispersant, spray granulation and reducing sintering, to obtain high-entropy alloy powder with excellent performance, and coating is prepared by plasma spraying and heat treatment, supplemented by dynamic reduction of magnetic field to improve deposition efficiency and structural optimization.

Benefits of technology

The high mechanical properties, corrosion resistance and wave absorption characteristics of FeCoNiMnAl high-entropy alloy coating are achieved, especially in high-frequency bands and high-temperature environments. The coating hardness is increased by 20%-30%, the corrosion rate is reduced, and the service life of high-temperature is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120205827A_ABST
    Figure CN120205827A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of high-entropy alloy powder and a preparation method of the obtained powder and coating, in particular to the technical field of high-entropy alloy, and the preparation method comprises the steps that metal precursor powder, an adhesive and a dispersing agent are mixed to obtain slurry; carrying out spray granulation on the obtained slurry to obtain precursor powder; and the obtained precursor powder is subjected to reduction sintering, and the FeCoNiMnAl high-entropy alloy powder is obtained. According to the preparation method provided by the invention, a specific preparation process is adopted, so that when the prepared FeCoNiMnAl high-entropy alloy powder is used as a raw material for plasma spraying, the FeCoNiMnAl high-entropy alloy coating with excellent performance can be obtained, and the preparation of the coating with relatively high mechanical property, corrosion resistance and wave-absorbing property is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-entropy alloys, and particularly to a method for preparing a high-entropy alloy powder, and a method for preparing the obtained powder and coating. Background Art

[0002] High-entropy alloys are usually composed of five or more elements. The high mixing entropy effect helps to form a simple solid solution or amorphous structure. Different from traditional intermetallic compounds or complex phase structures, high-entropy alloys have lower free energy and higher phase stability. The special composition design and phase structure in high-entropy alloys endow high-entropy alloys with excellent mechanical properties such as high strength and high wear resistance, as well as other special properties.

[0003] As a kind of high-entropy alloy, FeCoNiMnAl has excellent mechanical properties, corrosion resistance and relatively high electromagnetic wave absorption efficiency. The FeCoNiMnAl high-entropy alloy has a lattice distortion effect of a multi-principal element solid solution due to solid solution strengthening, a grain boundary strengthening effect, and a high-entropy effect that reduces the element diffusion rate, making it have higher hardness and wear resistance. In addition, the multi-principal element design can bring better thermal stability and high-temperature oxidation resistance. Because multiple elements act together, element diffusion is reduced, and a dense oxide layer is formed. In terms of corrosion resistance, high-entropy alloys can perform better in some corrosion environments due to their complex composition.

[0004] CN119681271A and CN117363922A respectively disclose a method for preparing a FeCoNiMnAl high-entropy alloy powder, but do not give further downstream processing techniques for the powder, nor mention whether it is applicable to the thermal spraying process. Therefore, there is an urgent need for a suitable and advanced processing technique to expand the application of the FeCoNiMnAl high-entropy alloy powder to ensure the realization of its excellent properties.

[0005] Atmospheric plasma spraying is a preparation technique that uses the plasma generated by arc discharge as a heat source to heat the coating powder to a molten or semi-molten state, and then atomizes it through a high-speed gas flow, and is sprayed and deposited on the substrate surface at a high speed. Compared with other spraying techniques, atmospheric plasma spraying has a faster preparation speed, higher deposition efficiency, simple operation procedures, and relatively low cost. However, conventional atmospheric plasma spraying techniques still need to be improved due to problems such as oxidation during spraying, over-melting of powder particles, element burning loss, uneven distribution of powder components in the plasma jet, and low deposition efficiency. There are still defects in the performance of the obtained coating under extreme working conditions such as high temperature, high wear, and strong corrosion (such as aero-engine blades, gas turbine components, high-temperature molds, offshore platform structures, etc.). Summary of the Invention

[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a high-entropy alloy powder and a method for preparing the obtained powder and coating, so as to solve the defects that the FeCoNiMnAl high-entropy alloy still has poor mechanical properties, corrosion resistance and bonding properties with the substrate when used as a coating.

[0007] To achieve this purpose, the present invention adopts the following technical solutions: In the first aspect, the present invention provides a method for preparing a FeCoNiMnAl high-entropy alloy powder, and the preparation method includes: Mixing a metal precursor powder, a binder and a dispersant to obtain a slurry; Performing spray granulation on the slurry to obtain a precursor powder; Performing reduction sintering on the precursor powder to obtain a FeCoNiMnAl high-entropy alloy powder.

[0008] The preparation method provided by the present invention, through adopting a specific preparation process, enables the obtained FeCoNiMnAl high-entropy alloy powder to obtain an FeCoNiMnAl high-entropy alloy coating with excellent properties when used as a raw material for plasma spraying, which is beneficial to realizing the preparation of a coating with high mechanical properties, corrosion resistance and wave absorption characteristics.

[0009] As a preferred technical solution of the present invention, the atomic ratio of Fe, Co, Ni, Mn and Al in the metal precursor powder is 1:1:1:1:0.5, and the specific surface area > 50m 2 / g.

[0010] Preferably, the metal precursor powder is obtained by coprecipitation and calcination.

[0011] Preferably, the coprecipitation includes: mixing a metal salt solution and an ammonium salt solution to carry out a coprecipitation reaction at a pH value of 8.5 - 9.

[0012] Preferably, the temperature of the coprecipitation reaction is 60 - 80°C.

[0013] Preferably, stirring with a stirring speed of 400 - 500 r / min is assisted in the coprecipitation reaction.

[0014] Preferably, the aging time of the coprecipitation reaction is ≥2 h.

[0015] Preferably, the calcination includes: calcining at 450 - 550°C for ≥2 h in an air atmosphere.

[0016] As a preferred technical solution of the present invention, the mass percentage content of the binder in the slurry is 1 - 2%.

[0017] Preferably, the mass percentage content of the dispersant in the slurry is 0.5 - 1%.

[0018] Preferably, the viscosity of the slurry is 200 - 300 mPa·s.

[0019] Preferably, the solid content of the slurry is 25 - 30%.

[0020] Preferably, the rotation speed of the atomizer in the spray granulation is 18000 - 20000 r / min.

[0021] Preferably, the feeding rate of the spray granulation is 20 - 30 mL / min.

[0022] Preferably, the temperature at the feeding port of the spray granulation is 220 - 250 °C.

[0023] Preferably, the temperature at the discharging port of the spray granulation is 90 - 100 °C.

[0024] As a preferred technical solution of the present invention, the sintering atmosphere of the reduction sintering includes: hydrogen.

[0025] Preferably, the gas flow rate for forming the sintering atmosphere in the reduction sintering is 4 - 6 L / min.

[0026] Preferably, the heating-up process of the reduction sintering is as follows: when the temperature is < 600 °C, the heating-up rate is 4 - 6 °C / min; when the temperature is ≥ 600 °C, the heating-up rate is 10 - 12 °C / min.

[0027] Preferably, the holding temperature of the reduction sintering is 1100 - 1200 °C.

[0028] Preferably, the holding time of the reduction sintering is ≥ 3 h.

[0029] Preferably, after the reduction sintering, the FeCoNiMnAl high-entropy alloy powder is obtained by furnace cooling.

[0030] In the second aspect, the present invention provides a FeCoNiMnAl high-entropy alloy powder, which is obtained by the preparation method described in the first aspect. The Hall flow rate of the FeCoNiMnAl high-entropy alloy powder is 22 - 26 s / 50 g, the oxygen mass percentage content is ≤ 0.3%, and the sphericity is > 90%.

[0031] In the third aspect, the present invention provides a preparation method of a FeCoNiMnAl high-entropy alloy coating, and the preparation method includes: Using the FeCoNiMnAl high-entropy alloy powder described in the second aspect as a raw material for plasma spraying, and then performing heat treatment to obtain a FeCoNiMnAl high-entropy alloy coating; During the plasma spraying, a dynamic magnetic field reduction is supplemented; The dynamic magnetic field reduction includes: a first magnetic field, a second magnetic field, and a third magnetic field that are sequentially reduced; The duration of the first magnetic field is 20 - 22% of the plasma spraying time; The duration of the second magnetic field is 60 - 62% of the plasma spraying time.

[0032] As a preferred technical solution of the present invention, the surface roughness Ra of the substrate used in the plasma spraying is 5 - 7 μm.

[0033] Preferably, the D50 particle size of the FeCoNiMnAl high-entropy alloy powder used in the plasma spraying is 15 - 45 μm, and the sphericity > 90%.

[0034] As a preferred technical solution of the present invention, the power of the plasma spraying is 35 - 50 kW.

[0035] Preferably, the main gas flow rate of the plasma spraying is 40 - 50 SLPM.

[0036] Preferably, the auxiliary gas flow rate of the plasma spraying is 10 - 15 SLPM.

[0037] Preferably, the scanning speed of the plasma spraying is 120 - 180 m / min.

[0038] Preferably, the powder feeding rate of the plasma spraying is 20 - 40 g / min.

[0039] Preferably, the distance between the plasma spraying gun nozzle and the substrate surface is 100 - 150 mm.

[0040] Preferably, the temperature of the substrate surface during the plasma spraying is 50 - 150 °C.

[0041] As a preferred technical solution of the present invention, the magnetic field strength of the first magnetic field is 1 - 1.2 T.

[0042] Preferably, the magnetic field strength of the second magnetic field is 0.8 - 1 T.

[0043] Preferably, the magnetic field strength of the third magnetic field is 0.5 - 0.8 T.

[0044] Preferably, the distribution uniformity of the magnetic field in the dynamic magnetic field reduction is ≤ 3%.

[0045] As a preferred technical solution of the present invention, a magnetic field of 0.3 - 0.5 T is supplemented during the heat treatment.

[0046] Preferably, the holding temperature of the heat treatment is 400 - 600 °C.

[0047] Preferably, the holding time of the heat treatment is ≥1 h.

[0048] Compared with the prior art solutions, the present invention has the following beneficial effects: (1) During the process of atmospheric plasma spraying the FeCoNiMnAl coating, by introducing a gradient magnetic field, the acceleration and aggregation of the plasma cause changes in the spraying speed of magnetic metal particles, which can improve the uniform distribution of magnetic metal particles in the plasma flame with a magnetic field. The aggregation and confinement effect of the magnetic field on the plasma reduces the non-uniformity and scattering phenomenon of the sprayed material particles, which helps to improve the quality of the coating; the core of this process is to use the magnetic field to affect the movement trajectory and distribution of charged particles in the plasma, so that ferromagnetic particles (such as Fe, Co charged particles) can be uniformly deposited into the coating in a constant magnetic field, and ferromagnetic particles are gradually deposited into the coating in a gradient magnetic field; (2) In a magnetic field of 0.5 - 1.2 T, ferromagnetic particles (such as Fe, Co charged particles) are affected by the magnetic moment orientation effect and form a special crystal structure along the magnetic field direction. The FeCoNiMnAl high-entropy alloy coating, relying on its multi-principal element synergistic effect and adjustable electromagnetic characteristics, the magnetic field optimizes the grain orientation of magnetic examples, enhances the magnetic anisotropy, and shows significant potential in the field of microwave absorption, especially having unique advantages in the high-frequency band (X / Ku band) and high-temperature environment. Further, the magnetic field-assisted plasma spraying process changes the trajectory of charged particles by applying a transverse magnetic field, increasing the deposition efficiency to 80 - 85%, and the special structural orientation can increase the coating hardness by 20% - 30%; (3) In the process of spraying, depositing, and cooling the high-entropy alloy coating in the present invention, there are nano-precipitation phases: in-situ generated B2 / L12 ordered phases (size <50 nm), which greatly improve the fracture toughness of the coating compared with traditional coatings of the same kind of elements. At the same time, the coating rapidly forms some amorphous tissues during the deposition and cooling in CO2 gas. During the service process, the coating has an effect of suppressing dynamic recrystallization: the high-entropy effect reduces the element diffusion rate (the diffusion coefficient is reduced by 2 orders of magnitude), and the high-entropy alloy can achieve the effect of suppressing the upward diffusion of matrix elements (especially such as Ti), greatly improving the service life of the coating in a high-temperature environment. In terms of corrosion resistance, the coating has an element synergistic effect: Fe / Co / Ni delays the penetration of Cl⁻ and can increase the critical pitting potential, effectively reducing the corrosion rate of the coating. Description of the Drawings

[0049] Figure 1 is the XRD diffraction pattern of the FeCoNiMnAl high-entropy alloy coating obtained in Example 1 of the present invention.

[0050] Figure 2It is the SEM photograph of the FeCoNiMnAl high-entropy alloy coating obtained in Example 1 of the present invention.

[0051] The present invention will be further described in detail below. However, the following examples are merely simple examples of the present invention and do not represent or limit the scope of the claimed protection of the present invention. The scope of protection of the present invention shall be subject to the claims. Detailed implementation manners

[0052] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the typical but non-limiting embodiments of the present invention are as follows: Currently, when preparing the FeCoNiMnAl high-entropy alloy coating by atmospheric plasma spraying, due to the poor matching between the used FeCoNiMnAl high-entropy alloy powder and plasma spraying, the performance of the coating obtained by plasma spraying is not good, such as poor mechanical properties, corrosion resistance and bonding properties, and it cannot be applied to relatively harsh working conditions. Based on this, the present invention proposes a preparation method of FeCoNiMnAl high-entropy alloy powder to ensure good matching between the obtained powder and plasma spraying, thereby ensuring the performance of the obtained FeCoNiMnAl high-entropy alloy coating, which is specifically as follows: This embodiment provides a preparation method of FeCoNiMnAl high-entropy alloy powder, and the preparation method includes: Mix the metal precursor powder, binder and dispersant to obtain a slurry; Perform spray granulation on the slurry to obtain a precursor powder; Perform reduction sintering on the precursor powder to obtain FeCoNiMnAl high-entropy alloy powder.

[0053] Among them, the atomic ratio of Fe, Co, Ni, Mn and Al in the metal salt precursor solution is 1:1:1:1:0.5, and the specific surface area > 50m 2 / g.

[0054] Among them, the metal precursor powder is obtained by co-precipitation and calcination.

[0055] Among them, the co-precipitation includes: mixing the metal salt solution and the ammonium salt solution to carry out a co-precipitation reaction at a pH value of 8.5 - 9. For example, it can be 8.5, 8.6, 8.7, 8.8, 8.9 or 9, etc., but is not limited to the listed values, and other unlisted values within this range also meet the requirements.

[0056] In the present invention, the metal salt solution is obtained by mixing the elements Fe, Co, Ni, Mn and Al in an atomic ratio using soluble salts in water, such as sulfate, nitrate, chloride, etc., and the ammonium salt solution can be, for example, a solution of ammonium bicarbonate and / or ammonium carbonate.

[0057] Among them, the total mass concentration of the metal salt solution is 4 - 5 mol / L, the mass concentration of the ammonium salt solution is 1 - 2 mol / L, and the mass ratio of the metal salt solution to the ammonium salt solution during mixing is 1:(6 - 8).

[0058] Among them, the total mass concentration of the metal salt solution is 4 - 5 mol / L. For example, it can be 4 mol / L, 4.1 mol / L, 4.2 mol / L, 4.3 mol / L, 4.4 mol / L, 4.5 mol / L, 4.6 mol / L, 4.7 mol / L, 4.8 mol / L, 4.9 mol / L or 5 mol / L, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0059] Among them, the mass concentration of the ammonium salt solution is 1 - 2 mol / L. For example, it can be 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2 mol / L, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0060] Among them, the mass ratio of the metal salt solution to the ammonium salt solution during mixing is 1:(6 - 8). For example, it can be 1:6, 1:6.2, 1:6.4, 1:6.6, 1:6.8, 1:7, 1:7.2, 1:7.4, 1:7.6, 1:7.8 or 1:8, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0061] Among them, the temperature of the coprecipitation reaction is 60 - 80 °C. For example, it can be 60 °C, 65 °C, 70 °C, 75 °C or 80 °C, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0062] Among them, stirring is assisted during the coprecipitation reaction at a stirring speed of 400 - 500 r / min. For example, it can be 400 r / min, 420 r / min, 440 r / min, 460 r / min, 480 r / min or 500 r / min, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0063] Among them, the aging time of the coprecipitation reaction is ≥2 h. For example, it can be 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0064] Among them, the calcination includes: calcining at 450 - 550°C for ≥2 h in an air atmosphere. The calcination temperature can be 450°C, 460°C, 480°C, 500°C, 520°C, 540°C, 550°C, etc., and the calcination time can be 2 h, 3 h, 4 h, 5 h, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0065] Among them, the mass percentage content of the binder in the slurry is 1 - 2%. For example, it can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0066] Among them, the mass percentage content of the dispersant in the slurry is 0.5 - 1%. For example, it can be 0.5%, 0.55%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95% or 1%, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0067] In the present invention, the dispersant used in spray granulation can be a commonly used dispersant in the art, such as ammonium polyacrylate (with a polymerization degree of 20 - 50), etc.

[0068] In the present invention, the binder used in spray granulation can be a commonly used binder in the art, such as polyvinyl alcohol (with a polymerization degree of 500 - 2000), etc.

[0069] Among them, the viscosity of the slurry is 200 - 300 mPa·s. For example, it can be 200 mPa·s, 210 mPa·s, 220 mPa·s, 230 mPa·s, 240 mPa·s, 250 mPa·s, 260 mPa·s, 270 mPa·s, 280 mPa·s, 290 mPa·s or 300 mPa·s, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0070] Among them, the solid content of the slurry is 25 - 30%. For example, it can be 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5% or 30%, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0071] Among them, the rotation speed of the atomizer in the spray granulation is 18,000 - 20,000 r / min. For example, it can be 18,000 r / min, 18,500 r / min, 19,000 r / min, 19,500 r / min, or 20,000 r / min, etc., but it is not limited to the listed values, and other unlisted values within this range also meet the requirements.

[0072] Among them, the feeding rate of the spray granulation is 20 - 30 mL / min. For example, it can be 20 mL / min, 22 mL / min, 24 mL / min, 26 mL / min, 28 mL / min, or 30 mL / min, etc., but it is not limited to the listed values, and other unlisted values within this range also meet the requirements.

[0073] Among them, the temperature at the feeding port of the spray granulation is 220 - 250 °C. For example, it can be 220 °C, 225 °C, 230 °C, 235 °C, 240 °C, 245 °C, or 250 °C, etc., but it is not limited to the listed values, and other unlisted values within this range also meet the requirements.

[0074] Among them, the temperature at the discharging port of the spray granulation is 90 - 100 °C. For example, it can be 90 °C, 92 °C, 94 °C, 96 °C, 98 °C, or 100 °C, etc., but it is not limited to the listed values, and other unlisted values within this range also meet the requirements.

[0075] Among them, the sintering atmosphere of the reduction sintering includes: hydrogen.

[0076] Among them, the gas flow rate for forming the sintering atmosphere in the reduction sintering is 4 - 6 L / min. For example, it can be 4 L / min, 4.5 L / min, 5 L / min, 5.5 L / min, or 6 L / min, etc., but it is not limited to the listed values, and other unlisted values within this range also meet the requirements.

[0077] Among them, the heating process of the reduction sintering is as follows: when the temperature is < 600 °C, the heating rate is 4 - 6 °C / min; when the temperature is ≥ 600 °C, the heating rate is 10 - 12 °C / min. The heating rate when the temperature is < 600 °C can be, for example, 4 °C / min, 4.5 °C / min, 5 °C / min, 5.5 °C / min, or 6 °C / min, etc.; the heating rate when the temperature is ≥ 600 °C can be, for example, 10 °C / min, 10.5 °C / min, 11 °C / min, 11.5 °C / min, or 12 °C / min, etc., but it is not limited to the listed values, and other unlisted values within this range also meet the requirements.

[0078] Among them, the holding temperature of the reduction sintering is 1100 - 1200 °C. For example, it can be 1100 °C, 1120 °C, 1140 °C, 1160 °C, 1180 °C or 1200 °C, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0079] Among them, the holding time of the reduction sintering is ≥ 3 h. For example, it can be 3 h, 3.5 h, 4 h, 4.5 h or 5 h, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0080] Among them, the FeCoNiMnAl high-entropy alloy powder is obtained by furnace cooling after the reduction sintering.

[0081] Furthermore, this embodiment provides a FeCoNiMnAl high-entropy alloy powder, which is obtained by the preparation method as described above. The Hall flow rate of the FeCoNiMnAl high-entropy alloy powder is 22 - 26 s / 50 g, the oxygen mass percentage content is ≤ 0.3%, and the sphericity is > 90%.

[0082] Furthermore, although the performance of the coating obtained through the aforementioned optimization is already relatively excellent, there are still certain defects. Based on this, the present invention further optimizes the coating preparation process, further improving the service performance of the obtained coating, specifically as follows: This embodiment provides a preparation method of a FeCoNiMnAl high-entropy alloy coating, and the preparation method includes: Using the FeCoNiMnAl high-entropy alloy powder as described above as the raw material for plasma spraying, and then performing heat treatment to obtain the FeCoNiMnAl high-entropy alloy coating; In the plasma spraying, a dynamic magnetic field reduction is supplemented; The dynamic magnetic field reduction includes: a first magnetic field, a second magnetic field, and a third magnetic field that are sequentially reduced.

[0083] Among them, the holding time of the first magnetic field is 20 - 22% of the plasma spraying time. For example, it can be 20%, 20.5%, 21%, 21.5% or 22%, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0084] Among them, the holding time of the second magnetic field is 60 - 62% of the plasma spraying time. For example, it can be 60%, 60.5%, 61%, 61.5% or 62%, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0085] Among them, excluding the holding time of the first magnetic field and the holding time of the second magnetic field, the remaining time is for maintaining the third magnetic field.

[0086] Among them, the surface roughness Ra of the substrate used in the plasma spraying is 5-7 μm. For example, it can be 5 μm, 5.5 μm, 6 μm, 6.5 μm or 7 μm, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0087] In the present invention, the substrate used for plasma spraying can be selected as workpieces such as aeroengine blades, gas turbine components, high-temperature molds, offshore platform structural members, etc. The specific materials are such as nickel-based superalloys or titanium alloys, etc. The specific spraying time can be reasonably selected according to the thickness of the required coating.

[0088] The D50 particle size of the FeCoNiMnAl high-entropy alloy powder used in the plasma spraying is 15-45 μm, and the sphericity > 90%. The D50 particle size can be, for example, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm or 45 μm, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0089] Among them, the power of the plasma spraying is 35-50 kW. For example, it can be 35 kW, 36 kW, 38 kW, 40 kW, 42 kW, 44 kW, 46 kW, 48 kW or 50 kW, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0090] The main gas flow rate of the plasma spraying is 40-50 SLPM. For example, it can be 40 SLPM, 42 SLPM, 44 SLPM, 46 SLPM, 48 SLPM or 50 SLPM, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0091] The auxiliary gas flow rate of the plasma spraying is 10-15 SLPM. For example, it can be 10 SLPM, 11 SLPM, 12 SLPM, 13 SLPM, 14 SLPM or 15 SLPM, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0092] In the present invention, the main gas and auxiliary gas used in the plasma spraying can be specifically selected and designed according to the conventional requirements in the art. For example, argon is selected as the main gas, and hydrogen and / or helium are selected as the auxiliary gas, etc.

[0093] The scanning speed of the plasma spraying is 120-180 m / min. For example, it can be 120 m / min, 130 m / min, 140 m / min, 150 m / min, 160 m / min, 170 m / min or 180 m / min, etc., but not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0094] The powder feeding rate of the plasma spraying is 20 - 40 g / min. For example, it can be 20 g / min, 25 g / min, 30 g / min, 35 g / min, 40 g / min, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0095] In the plasma spraying, the distance between the spray gun nozzle and the substrate surface is 100 - 150 mm. For example, it can be 100 mm, 110 mm, 120 mm, 130 mm, 140 mm, 150 mm, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0096] In the plasma spraying, the temperature of the substrate surface is 50 - 150 °C. For example, it can be 50 °C, 60 °C, 80 °C, 100 °C, 120 °C, 140 °C, 150 °C, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0097] Among them, the magnetic field strength of the first magnetic field is 1 - 1.2 T. For example, it can be 1 T, 1.05 T, 1.1 T, 1.15 T, 1.2 T, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0098] The magnetic field strength of the second magnetic field is 0.8 - 1 T. For example, it can be 0.8 T, 0.85 T, 0.9 T, 0.95 T, 1 T, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0099] The magnetic field strength of the third magnetic field is 0.5 - 0.8 T. For example, it can be 0.5 T, 0.55 T, 0.6 T, 0.65 T, 0.7 T, 0.75 T, 0.8 T, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0100] In the dynamic reduction magnetic field, the distribution uniformity of the magnetic field ≤ 3%. For example, it can be 3%, 2.5%, 2%, 1.5%, 1%, 0.5%, 0.1%, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0101] In the present invention, the distribution uniformity of the magnetic field refers to that within a certain volume, the magnetic induction intensity fluctuation of the magnetic field within the spraying range ≤ 3%.

[0102] Among them, in the heat treatment, a magnetic field of 0.3 - 0.5 T is supplemented. For example, it can be 0.3 T, 0.35 T, 0.4 T, 0.45 T, 0.5 T, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0103] The holding temperature of the heat treatment is 400-600 °C. For example, it can be 400 °C, 450 °C, 500 °C, 550 °C or 600 °C, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0104] The holding time of the heat treatment is ≥1 h. For example, it can be 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc., but is not limited to the listed values. Other unlisted values within this range also meet the requirements.

[0105] Furthermore, in order to illustrate the effects that can be achieved when preparing the coating using the FeCoNiMnAl high-entropy alloy powder provided by the present invention, the following exemplary scheme is used for illustrative description, specifically as follows.

[0106] Example 1: This example provides a preparation method and utilization process of FeCoNiMnAl high-entropy alloy powder, specifically as follows: Mix the metal precursor powder, binder and dispersant to obtain a slurry; Perform spray granulation on the obtained slurry to obtain a precursor powder; Perform reduction sintering on the obtained precursor powder to obtain FeCoNiMnAl high-entropy alloy powder; The metal precursor powder is obtained by co-precipitation and calcination; the co-precipitation includes: mixing a metal salt solution with a total molar concentration of 4.5 mol / L (mixing elements Fe, Co, Ni, Mn and Al according to the atomic ratio using soluble sulfates in water) and an ammonium salt solution with a molar concentration of 1.5 mol / L (ammonium carbonate) in a mass ratio of 1:7, and then performing a co-precipitation reaction at a pH value of 8.8. The temperature of the co-precipitation reaction is 70 °C, assisted by stirring at a stirring speed of 450 r / min, and aging for 2 h; the calcination includes: calcining at 500 °C for 2 h in an air atmosphere; the atomic ratio of Fe, Co, Ni, Mn and Al in the obtained metal precursor powder is 1:1:1:1:0.5, and the specific surface area is 60 m 2 / g; The mass percentage content of the binder (polyvinyl alcohol, polymerization degree of 1250) in the slurry is 1.5%, the mass percentage content of the dispersant (ammonium polyacrylate, polymerization degree of 35) is 0.8%, the viscosity of the slurry is 250 mPa·s, and the solid content of the slurry is 28%; In the spray granulation, the atomizer rotation speed is 19000 r / min, the feeding rate is 25 mL / min, the feeding port temperature is 235 °C, and the discharging port temperature is 95 °C; The sintering atmosphere for the reduction sintering includes: hydrogen, the gas flow rate for forming the sintering atmosphere is 5 L / min, the heating process is as follows: when the temperature is <600 °C, the heating rate is 5 °C / min, when the temperature is ≥600 °C, the heating rate is 11 °C / min, the holding temperature is 1150 °C, the holding time is 3 h, and after the reduction sintering, the FeCoNiMnAl high-entropy alloy powder is obtained by furnace cooling.

[0107] Furthermore, the obtained powder is used as the powder raw material for plasma spraying to prepare a coating, which is specifically as follows: FeCoNiMnAl high-entropy alloy powder is used as the raw material for plasma spraying, and then heat treatment is carried out to obtain the FeCoNiMnAl high-entropy alloy coating; In the plasma spraying, the surface roughness Ra of the substrate used is 6 μm, the D50 particle size of the FeCoNiMnAl high-entropy alloy powder used is 30 μm, the sphericity is 95%, and the Hall flow rate is 24 s / 50 g; The power of the plasma spraying is 40 kW, the main gas (argon) flow rate is 45 SLPM, the auxiliary gas (helium) flow rate is 12 SLPM, the scanning speed is 150 m / min, the powder feeding rate is 30 g / min, the distance between the spray gun nozzle and the substrate surface is 125 mm, and the temperature of the substrate surface is 100 °C; The holding temperature of the heat treatment is 500 °C, and the holding time is 1 h.

[0108] Example 2: This example provides a preparation method and utilization process of FeCoNiMnAl high-entropy alloy powder, which is specifically as follows: The metal precursor powder, binder, and dispersant are mixed to obtain a slurry; The obtained slurry is spray granulated to obtain the precursor powder; The obtained precursor powder is subjected to reduction sintering to obtain the FeCoNiMnAl high-entropy alloy powder; The metal precursor powder is obtained by co-precipitation and calcination; the co-precipitation includes: mixing a metal salt solution with a total molar concentration of 5 mol / L (mixing elements Fe, Co, Ni, Mn, and Al according to the atomic ratio using soluble sulfates in water) and an ammonium salt solution with a molar concentration of 1 mol / L (ammonium carbonate) according to a mass ratio of 1:6, and then carrying out a co-precipitation reaction at a pH value of 9. The temperature of the co-precipitation reaction is 80 °C, supplemented with stirring at a stirring speed of 500 r / min, and aging for 2 h; the calcination includes: calcining at 550 °C for 2 h in an air atmosphere; the atomic ratio of Fe, Co, Ni, Mn, and Al in the obtained metal precursor powder is 1:1:1:1:0.5, and the specific surface area is 80 m 2 / g; The mass percentage content of the binder (polyvinyl alcohol with a degree of polymerization of 500) in the slurry is 2%, the mass percentage content of the dispersant (ammonium polyacrylate with a degree of polymerization of 50) is 1%, the viscosity of the slurry is 200 mPa·s, and the solid content of the slurry is 30%; In the spray granulation, the rotation speed of the atomizer is 20000 r / min, the feeding rate is 20 mL / min, the temperature at the feeding port is 250 °C, and the temperature at the discharging port is 100 °C; The sintering atmosphere for the reduction sintering includes: hydrogen, the gas flow rate for forming the sintering atmosphere is 6 L / min, the heating process is as follows: when the temperature is <600 °C, the heating rate is 6 °C / min, when the temperature is ≥600 °C, the heating rate is 10 °C / min, the holding temperature is 1200 °C, the holding time is 3 h, and after the reduction sintering, the FeCoNiMnAl high-entropy alloy powder is obtained through furnace cooling.

[0109] Furthermore, the obtained powder is used as the powder raw material for plasma spraying to prepare the coating, specifically as follows: FeCoNiMnAl high-entropy alloy powder is used as the raw material for plasma spraying, and then heat treatment is carried out to obtain the FeCoNiMnAl high-entropy alloy coating; In the plasma spraying, the surface roughness Ra of the substrate used is 7 μm, the D50 particle size of the FeCoNiMnAl high-entropy alloy powder used is 45 μm, the sphericity is 96%, and the Hall flow rate is 22 s / 50 g; The power of the plasma spraying is 50 kW, the main gas (argon) flow rate is 50 SLPM, the auxiliary gas (helium) flow rate is 10 SLPM, the scanning speed is 180 m / min, the powder feeding rate is 20 g / min, the distance between the spray gun nozzle and the substrate surface is 150 mm, and the temperature of the substrate surface is 50 - 150 °C; The holding temperature of the heat treatment is 600 °C, and the holding time is 1 h.

[0110] Example 3: This example provides a preparation method and utilization process of FeCoNiMnAl high-entropy alloy powder, specifically as follows: The metal precursor powder, binder, and dispersant are mixed to obtain a slurry; The obtained slurry is spray granulated to obtain the precursor powder; The obtained precursor powder is subjected to reduction sintering to obtain the FeCoNiMnAl high-entropy alloy powder; The metal precursor powder is obtained by co-precipitation and calcination; the co-precipitation includes: mixing a metal salt solution with a total molar concentration of 4 mol / L (mixing elements Fe, Co, Ni, Mn, and Al in an atomic ratio using soluble sulfates in water) and an ammonium salt solution with a molar concentration of 2 mol / L (ammonium bicarbonate) according to a mass ratio of 1:8, then carrying out a co-precipitation reaction at a pH value of 8.5, the temperature of the co-precipitation reaction is 60 °C, assisted by stirring at a stirring speed of 400 r / min, and aging for 3 h; the calcination includes: calcining at 450 °C for 4 h in an air atmosphere; the atomic ratio of Fe, Co, Ni, Mn, and Al in the obtained metal precursor powder is 1:1:1:1:0.5, and the specific surface area is 70 m 2 / g; The mass percentage content of the binder (polyvinyl alcohol with a polymerization degree of 2000) in the slurry is 1%, the mass percentage content of the dispersant (ammonium polyacrylate with a polymerization degree of 20) is 0.5%, the viscosity of the slurry is 300 mPa·s, and the solid content of the slurry is 25%; In the spray granulation, the rotational speed of the atomizer is 18000 r / min, the feeding rate is 30 mL / min, the temperature at the feeding port is 220 °C, and the temperature at the discharging port is 90 °C; The sintering atmosphere for the reduction sintering is hydrogen, the gas flow rate for forming the sintering atmosphere is 4 L / min, the heating process is as follows: when <600 °C, the heating rate is 4 °C / min, when ≥600 °C, the heating rate is 12 °C / min, the holding temperature is 1100 °C, the holding time is 4 h, and after the reduction sintering, the FeCoNiMnAl high-entropy alloy powder is obtained by furnace cooling.

[0111] Furthermore, the obtained powder is used as the powder raw material for plasma spraying to prepare a coating, specifically as follows: Using the FeCoNiMnAl high-entropy alloy powder as the raw material for plasma spraying, and then carrying out heat treatment to obtain the FeCoNiMnAl high-entropy alloy coating; In the plasma spraying, the surface roughness Ra of the substrate used is 5 μm, the D50 particle size of the FeCoNiMnAl high-entropy alloy powder used is 15 μm, the sphericity is 92%, and the Hall flow rate is 26 s / 50 g; The power of the plasma spraying is 35 kW, the main gas (argon) flow rate is 40 SLPM, the auxiliary gas (hydrogen) flow rate is 15 SLPM, the scanning speed is 120 m / min, the powder feeding rate is 40 g / min, the distance between the spray gun nozzle and the substrate surface is 100 mm, and the temperature of the substrate surface is 50 - 150 °C; The holding temperature of the heat treatment is 400 °C, and the holding time is 3 h.

[0112] Comparative Example 1: The difference from Example 1 is only that the metal precursor is replaced with a metal elemental mixed powder composed of an equimolar amount.

[0113] Example 4: The difference from Example 1 is only that the solid content of the slurry is 20%.

[0114] Example 5: The difference from Example 1 is only that the solid content of the slurry is 35%.

[0115] Example 6: The difference from Example 1 is only that the calcination temperature is 800 °C.

[0116] Example 7: The difference from Example 1 is only that the holding temperature for reduction sintering is 650 °C.

[0117] When spraying the above examples and comparative examples, the substrate is nickel-based alloy inconel718, and the spraying time is 2 min. The mechanical properties and corrosion resistance of the coatings obtained from the above Examples 1-7 and Comparative Example 1 were tested. Among them, the microhardness of the coating was obtained according to the execution standard of GB / T 4340.1-2009, the fracture toughness of the coating was obtained according to the execution standard of ISO 12135 indentation method, the wear resistance of the coating was obtained by the ASTM G65 rubber wheel abrasive wear test standard test, and the corrosion resistance of the coating was obtained by GB / T 10125-2021: "Artificial Atmosphere Corrosion Test - Salt Spray Test" and GB / T4334-2020: "Corrosion of Metals and Alloys - Laboratory Immersion Test Method for Uniform Corrosion". The corrosion resistance measurement results of the coating are shown in Table 1 and Table 2 below. The XRD pattern of the coating obtained in Example 1 is as Figure 1 shown, and the SEM photos are as Figure 2 shown.

[0118] Table 1

[0119] Table 2

[0120] In Table 2, the concentration of the NaCl solution refers to the mass concentration, and the concentration of the H2SO4 solution refers to the mass concentration.

[0121] Furthermore, in order to clarify the effects that can be achieved by the magnetic field introduced during plasma spraying in the present invention, the following examples are used for illustration.

[0122] Example 8: The difference from Example 1 is only that a dynamically decreasing magnetic field is supplemented in the plasma spraying; the dynamically decreasing magnetic field includes: a first magnetic field, a second magnetic field, and a third magnetic field that decrease in sequence. The maintenance time of the first magnetic field is 21% of the plasma spraying time, the maintenance time of the second magnetic field is 61% of the plasma spraying time, and the remaining time is the maintenance time of the third magnetic field. The magnetic field intensity of the first magnetic field is 1.1 T, the magnetic field intensity of the second magnetic field is 0.9 T, the magnetic field intensity of the third magnetic field is 0.6 T, and the magnetic field distribution uniformity is 3%.

[0123] Example 9: The difference from Example 2 is only that a dynamically decreasing magnetic field is supplemented in the plasma spraying; the dynamically decreasing magnetic field includes: a first magnetic field, a second magnetic field, and a third magnetic field that decrease in sequence. The maintenance time of the first magnetic field is 20% of the plasma spraying time, the maintenance time of the second magnetic field is 62% of the plasma spraying time, and the remaining time is the maintenance time of the third magnetic field. The magnetic field intensity of the first magnetic field is 1 T, the magnetic field intensity of the second magnetic field is 0.8 T, the magnetic field intensity of the third magnetic field is 0.5 T, and the magnetic field distribution uniformity is 2%.

[0124] Example 10: The difference from Example 3 is only that a dynamically decreasing magnetic field is supplemented in the plasma spraying; the dynamically decreasing magnetic field includes: a first magnetic field, a second magnetic field, and a third magnetic field that decrease in sequence. The maintenance time of the first magnetic field is 22% of the plasma spraying time, the maintenance time of the second magnetic field is 60% of the plasma spraying time, and the remaining time is the maintenance time of the third magnetic field. The magnetic field intensity of the first magnetic field is 1.2 T, the magnetic field intensity of the second magnetic field is 1 T, the magnetic field intensity of the third magnetic field is 0.8 T, and the magnetic field distribution uniformity is 1%.

[0125] Example 11: The difference from Example 1 is only that a magnetic field of 0.4 T is supplemented in the heat treatment.

[0126] Example 12: The difference from Example 2 is only that a magnetic field of 0.3 T is supplemented in the heat treatment.

[0127] Example 13: The difference from Example 3 is only that a magnetic field of 0.5 T is supplemented in the heat treatment.

[0128] Example 14: The difference from Example 1 is only that a dynamically decreasing magnetic field is supplemented in the plasma spraying; the dynamically decreasing magnetic field includes: a first magnetic field, a second magnetic field, and a third magnetic field that decrease in sequence. The maintaining time of the first magnetic field is 21% of the plasma spraying time, the maintaining time of the second magnetic field is 61% of the plasma spraying time, and the remaining time is the maintaining time of the third magnetic field. The magnetic field intensity of the first magnetic field is 1.1 T, the magnetic field intensity of the second magnetic field is 0.9 T, the magnetic field intensity of the third magnetic field is 0.7 T, and the magnetic field distribution uniformity is 3%; A magnetic field of 0.4 T is supplemented in the heat treatment.

[0129] Example 15: The difference from Example 2 is only that a dynamically decreasing magnetic field is supplemented in the plasma spraying; the dynamically decreasing magnetic field includes: a first magnetic field, a second magnetic field, and a third magnetic field that decrease in sequence. The maintaining time of the first magnetic field is 20% of the plasma spraying time, the maintaining time of the second magnetic field is 60% of the plasma spraying time, and the remaining time is the maintaining time of the third magnetic field. The magnetic field intensity of the first magnetic field is 1 T, the magnetic field intensity of the second magnetic field is 0.8 T, the magnetic field intensity of the third magnetic field is 0.5 T, and the magnetic field distribution uniformity is 1%; A magnetic field of 0.5 T is supplemented in the heat treatment.

[0130] Example 16: The difference from Example 3 is only that a dynamically decreasing magnetic field is supplemented in the plasma spraying; the dynamically decreasing magnetic field includes: a first magnetic field, a second magnetic field, and a third magnetic field that decrease in sequence. The maintaining time of the first magnetic field is 22% of the plasma spraying time, the maintaining time of the second magnetic field is 62% of the plasma spraying time, and the remaining time is the maintaining time of the third magnetic field. The magnetic field intensity of the first magnetic field is 1.2 T, the magnetic field intensity of the second magnetic field is 1 T, the magnetic field intensity of the third magnetic field is 0.8 T, and the magnetic field distribution uniformity is 2%; A magnetic field of 0.3 T is supplemented in the heat treatment.

[0131] Example 17: The difference from Example 8 is only that a constant magnetic field with a magnetic field intensity of 0.8 T is supplemented in the plasma spraying.

[0132] Example 18: The difference from Example 8 is only that the application order of the first magnetic field and the third magnetic field is swapped, that is, the third magnetic field, the second magnetic field, and the first magnetic field are applied in sequence. At this time, it is a dynamically increasing magnetic field.

[0133] Example 19: The difference from Example 8 is only that the first magnetic field is not set, and the maintaining time of the first magnetic field is proportionally distributed to the second magnetic field and the third magnetic field.

[0134] Example 20: The difference from Example 8 is only that the second magnetic field is not provided, and the maintenance time of the second magnetic field is proportionally distributed to the first magnetic field and the third magnetic field.

[0135] Example 21: The difference from Example 8 is only that the third magnetic field is not provided, and the maintenance time of the third magnetic field is proportionally distributed to the first magnetic field and the second magnetic field.

[0136] Example 22: The difference from Example 11 is only that the intensity of the magnetic field supplemented in the heat treatment is 0.1 T.

[0137] Example 23: The difference from Example 11 is only that the intensity of the magnetic field supplemented in the heat treatment is 1 T.

[0138] The coatings obtained in Examples 8 - 23 were subjected to bond strength testing, mechanical property testing, and high - temperature oxidation resistance testing. Among them, the bond strength of the coatings was obtained by using GB / T 8642 - 2002: "Determination of Bond Strength of Thermal Sprayed Coatings", and the numerical value of the high - temperature oxidation resistance of the coatings was obtained by using the ASTM G54 standard. The results are shown in Table 3 below.

[0139] Table 3

[0140] In Table 3, the mass increment refers to the mass increased per unit area of the coating after oxidation at 1000 °C for 100 h.

[0141] As can be seen from Tables 1 - 3, the preparation method provided by the present invention, through the adoption of a specific preparation process, enables the obtained FeCoNiMnAl high - entropy alloy powder as the raw material for plasma spraying to obtain an FeCoNiMnAl high - entropy alloy coating with excellent performance, which is beneficial to the preparation of coatings with high mechanical properties, corrosion resistance, and wave - absorbing characteristics.

[0142] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above - mentioned embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0143] In addition, it should be noted that, among the various specific technical features described in the above - mentioned specific embodiments, they can be combined in any appropriate manner without contradiction. To avoid unnecessary repetition, the present invention will not separately describe various possible combination methods.

[0144] In addition, any combination can be made among various different embodiments of the present invention, as long as it does not violate the idea of the present invention, and it should equally be regarded as the content disclosed by the present invention.

Claims

1. A preparation method of FeCoNiMnAl high-entropy alloy powder, characterized in that, The preparation method includes: Mixing a metal precursor powder, a binder, and a dispersant to obtain a slurry; Performing spray granulation on the slurry to obtain a precursor powder; Performing reduction sintering on the precursor powder to obtain FeCoNiMnAl high-entropy alloy powder; The metal precursor powder is obtained by co-precipitation and calcination; the calcination includes: calcining at 450 - 550 °C for ≥2 h in an air atmosphere; The solid content of the slurry is 25 - 30%; the holding temperature of the reduction sintering is 1100 - 1200 °C.

2. The preparation method according to claim 1, characterized in that, The atomic ratio of Fe, Co, Ni, Mn, and Al in the metal precursor powder is 1:1:1:1:0.5, and the specific surface area > 50 m 2 / g; The co-precipitation includes: mixing a metal salt solution and an ammonium salt solution to perform a co-precipitation reaction at a pH value of 8.5 - 9; The temperature of the co-precipitation reaction is 60 - 80 °C; Stirring is assisted during the co-precipitation reaction at a stirring speed of 400 - 500 r / min; The aging time of the co-precipitation reaction is ≥2 h.

3. The preparation method according to claim 1, characterized in that, The mass percentage content of the binder in the slurry is 1 - 2%; The mass percentage content of the dispersant in the slurry is 0.5 - 1%; The viscosity of the slurry is 200 - 300 mPa·s; The rotational speed of the atomizer in the spray granulation is 18000 - 20000 r / min; The feeding rate of the spray granulation is 20 - 30 mL / min; The temperature of the feeding port of the spray granulation is 220 - 250 °C; The temperature of the discharging port of the spray granulation is 90 - 100 °C.

4. The preparation method according to claim 1, characterized in that, The sintering atmosphere of the reduction sintering includes: hydrogen; The gas flow rate for forming the sintering atmosphere in the reduction sintering is 4 - 6 L / min; The heating process of the reduction sintering is: when <600 °C, the heating rate is 4 - 6 °C / min, and when ≥600 °C, the heating rate is 10 - 12 °C / min; The holding time of the reduction sintering is ≥3 h; After the reduction sintering, the FeCoNiMnAl high-entropy alloy powder is obtained by furnace cooling.

5. A FeCoNiMnAl high-entropy alloy powder, characterized in that, The FeCoNiMnAl high-entropy alloy powder is obtained by the preparation method described in any one of claims 1 - 4. The Hall flow rate of the FeCoNiMnAl high-entropy alloy powder is 22 - 26 s / 50 g, the oxygen mass percentage content is ≤0.3%, and the sphericity is >90%.

6. A preparation method of a FeCoNiMnAl high-entropy alloy coating, characterized in that, The preparation method includes: Using the FeCoNiMnAl high-entropy alloy powder described in claim 5 as a raw material for plasma spraying, and then performing heat treatment to obtain a FeCoNiMnAl high-entropy alloy coating; A dynamic magnetic field reduction is assisted during the plasma spraying; The dynamic magnetic field reduction includes: a first magnetic field, a second magnetic field, and a third magnetic field that are sequentially reduced; The holding time of the first magnetic field is 20 - 22% of the plasma spraying time; The holding time of the second magnetic field is 60 - 62% of the plasma spraying time.

7. The preparation method according to claim 6, characterized in that, The surface roughness Ra of the substrate used in the plasma spraying is 5 - 7 μm; The D50 particle size of the FeCoNiMnAl high-entropy alloy powder used in the plasma spraying is 15 - 45 μm, and the sphericity is >90%.

8. The preparation method according to claim 6, wherein The power of the plasma spraying is 35 - 50 kW; The main gas flow rate of the plasma spraying is 40 - 50 SLPM; The auxiliary gas flow rate of the plasma spraying is 10 - 15 SLPM; The scanning speed of the plasma spraying is 120 - 180 m / min; The powder feeding rate of the plasma spraying is 20 - 40 g / min; The distance between the plasma spraying gun nozzle and the substrate surface is 100 - 150 mm; The temperature of the substrate surface during the plasma spraying is 50 - 150 °C.

9. The preparation method according to claim 6, wherein The magnetic field strength of the first magnetic field is 1 - 1.2 T; The magnetic field strength of the second magnetic field is 0.8 - 1 T; The magnetic field strength of the third magnetic field is 0.5 - 0.8 T; The distribution uniformity of the magnetic field in the dynamically reduced magnetic field is ≤ 3%; 10. The preparation method according to claim 6, characterized in that, A magnetic field of 0.3 - 0.5 T is applied during the heat treatment; The holding temperature of the heat treatment is 400 - 600 °C; The holding time of the heat treatment is ≥ 1 h.

Citation Information

Patent Citations

  • FeCoNiMnAl high-entropy alloy modified graphene foam composite material and preparation method thereof

    CN117363922A

  • Preparation method of FeCoNiMnAl series high-entropy alloy powder with wave absorbing performance

    CN119681271A

  • Formula and preparation method of pseudo high-entropy alloy coating

    CN108315686A

  • FeCoNiCrSiAl high-entropy alloy coating and preparation method thereof

    CN108677129A

  • FeCoNiCrMn high-entropy alloy and method for preparing wear-resisting coating through alloy

    CN109930053A